Potret Eksploitasi Anak sebagai Masalah Sosial dan Dampaknya terhadap Perkembangan Anak - Novebryan, Raffi Rizkytia; W, Wahyuningrum; Muling, Candra Wijaya; Nurwendha, Siti Ahdia; Wulan, Nandar; Putri, Sekar Rahayu; Cahayo, Raul Gindo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Child exploitation is one of the most severe human rights violations and remains a critical social issue in Indonesia, where children undergoing essential stages of physical, mental, and social development are highly vulnerable to coercion, pressure, and various harmful forms of exploitation ranging from economic, sexual, and emotional exploitation to the increasingly prevalent digital exploitation driven by technological advancement. Complex social and economic factors such as poverty, low parental education, weak social control, and the limited effectiveness of state protection further exacerbate children’s vulnerability. This study employs a descriptive qualitative method through literature review and analysis of reports from child protection institutions to describe the forms of exploitation, contributing factors, and their impacts on child development. The findings reveal that child exploitation leads to multidimensional consequences, including psychological trauma, physical health problems, social difficulties, and disruptions in moral and cognitive development that threaten the child’s future. These findings emphasize the necessity of a comprehensive approach to addressing child exploitation through collaboration among families, schools, communities, and the government by strengthening parental literacy, ensuring safe reporting mechanisms, empowering families economically, and enforcing consistent and equitable legal protection to guarantee children’s rights to grow and develop in a safe and supportive environment.